ATTITUDES TOWARD DRUGS IN E.G.B. STUDENTS FROM THE REGIÓN DE MURCIA (SPAIN) - Ortega Ruiz, Pedro; Mínguez Vallejos, Ramón; Pagán Martínez, Francisco A. (Anales de Psicología / Annals of Psychology)
A survey was conducted among 5263 high school students 11 to 14 years old in Murcia Region to find out about their attitudes towards drug consumption. Results indicate that the majority of pupils surveyed are not indicate that the majority of pupils surveyed are not familiar with the type of dangers involved in getting hooked on drugs. Another interesting finding reveals that consumption of alcoholic drinks is more and more accepted by adolescents.